5a - 2b = - 2
5a - 2b - (- 2b) = - 2 - (- 2b)
5a = - 2 - (- 2b)
5a = 2b - 2
5 a = (2b - 2) ÷ 5
a = (2b - 2) x 1/5
a = 2b x1/5 - 2 x 1/5
a = 2/5 b - 2 x 1/5
a = 2/5 b - 2/5
Solución:
-3a +7b = -22
- 3a = - 22 - (7b)
- 3a = - 7b - 22
3a = 7b + 22
a = (7b + 22) ÷ 3
a = (7b + 22) x 1/3
a = 7b x 1/3 + 22 x 1/3
a = 7/3 b + 22 x1/3
a = 7/3b + 22/3
solución:
Explicación paso a paso:
[tex] \blue{saludos}[/tex]
Respuesta:
5a _ 2b =2
3a + 7b=-22
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Verified answer
5a - 2b = - 2
5a - 2b - (- 2b) = - 2 - (- 2b)
5a = - 2 - (- 2b)
5a = 2b - 2
5 a = (2b - 2) ÷ 5
a = (2b - 2) x 1/5
a = 2b x1/5 - 2 x 1/5
a = 2/5 b - 2 x 1/5
a = 2/5 b - 2/5
Solución:
a = 2/5 b - 2/5
-------------------------------------------------
-3a +7b = -22
- 3a = - 22 - (7b)
- 3a = - 7b - 22
3a = 7b + 22
a = (7b + 22) ÷ 3
a = (7b + 22) x 1/3
a = 7b x 1/3 + 22 x 1/3
a = 7/3 b + 22 x1/3
a = 7/3b + 22/3
solución:
a = 7/3b + 22/3
Explicación paso a paso:
[tex] \blue{saludos}[/tex]
Respuesta:
Explicación paso a paso:
5a _ 2b =2
3a + 7b=-22